The impact of the availability of draivfood in increasing culinary business income in Baolan District, Tolitoli Regency - Yanto, Edi; Muzakkir, Abd.; Sikria, Reka; Arfandi, Masri; Nur, Jabal (Junal Ilmu Manajemen, 2025)
This study aims to determine the impact of the availability of Draivfood in increasing the income of culinary businesses and to find out the level of income before and after using Draivfood in Baolan sub-district, Tolitoli regency. This research uses a qualitative method. The data source is in the form of primary data obtained from the results of interviews and documentation. The data analysis techniques used are data reduction, data presentation and data verification. Based on the results of the study, it shows that the impact of the availability of Draivfood is very helpful for culinary business actors in increasing income, in addition to increasing the income of culinary business actors, it is revealed that Draivfood has an impact on increasing business popularity, making it easier to market products, and making it easier to deliver products. Culinary business actors revealed that there was an increase in income after joining Draivfood. Three out of nine culinary businesses have increased by more than 50%. Factors that contribute to increasing revenue for culinary businesses that join Draivfood are operating hours, production costs and the number of orders. Operating hours do not have a significant impact on increasing culinary business revenue, production costs are stable and do not experience a significant increase due to the efficiency generated by Draivfood and the increase in revenue that is balanced with the costs that must be incurred. Meanwhile, the visibility and ease of access provided by Draivfood increased the overall number of orders.